2002
DOI: 10.1021/ma020320y
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Study of Poly(N-propargylamides) Having Bulky Pendant Groups

Abstract: N-Propargylamides having chiral centers at the α-carbon of the amide groups, 1−3, were polymerized with (nbd)Rh+[η 6-C6H5B-(C6H5)3] to afford polymers with moderate molecular weights (M n = 6000−32 000) in good yield. The 1H NMR spectra demonstrated that the polymers have stereoregular structures (cis = 100%). The polymers were proven to take a helical conformation with an excess of one-handed screw sense in CHCl3, which was supported by their intense CD effects and large optical rotations. It was confirmed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
102
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 125 publications
(106 citation statements)
references
References 17 publications
(43 reference statements)
4
102
0
Order By: Relevance
“…94,95 The 1 H NMR spectra demonstrated that these polymers have cis-transoidal stereoregular structure. The intense CD effects and large optical rotations of the polymers in CHCl 3 indicated that they take helical conformation with one-handed screw sense.…”
Section: Helical Structurementioning
confidence: 96%
“…94,95 The 1 H NMR spectra demonstrated that these polymers have cis-transoidal stereoregular structure. The intense CD effects and large optical rotations of the polymers in CHCl 3 indicated that they take helical conformation with one-handed screw sense.…”
Section: Helical Structurementioning
confidence: 96%
“…It has been reported that the helical structure of poly(N-propargylamide)s is stabilized by the intramolecular hydrogen bonds between the pendant amide groups. [17] In polar solvents such as DMSO and water, therefore, the hydrogen bonds are readily broken to effect destabilization of the helical structure. The helical conformation of 6 in polar solvents is probably stabilized by the bulky substituents in the side chains of sugar and lauryloyl groups.…”
Section: Secondary Conformation Ofmentioning
confidence: 99%
“…[21] Other monomers were synthesized according to the methods introduced earlier (monomer 1, ref. [22] ; monomer 2, ref. [22] ; and monomer 3, ref.…”
Section: Experimental Part Materialsmentioning
confidence: 99%